2015
DOI: 10.1038/ncomms6862
|View full text |Cite|
|
Sign up to set email alerts
|

CCR7-dependent trafficking of RORγ+ ILCs creates a unique microenvironment within mucosal draining lymph nodes

Abstract: Presentation of peptide:MHCII by RORγ-expressing group 3 innate lymphoid cells (ILC3s), which are enriched within gut tissue, is required for control of CD4 T-cell responses to commensal bacteria. It is not known whether ILC populations migrate from their mucosal and peripheral sites to local draining secondary lymphoid tissues. Here we demonstrate that ILC3s reside within the interfollicular areas of mucosal draining lymph nodes, forming a distinct microenvironment not observed in peripheral lymph nodes. By p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
184
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 186 publications
(217 citation statements)
references
References 44 publications
(82 reference statements)
29
184
0
Order By: Relevance
“…To interrogate the levels of CD1d expression in the different ILC3 subpopulations, we performed additional phenotypical analyses of ILC3s from different tissues (Figs 1D and E, and EV1, EV2 and EV3). As previously described, we found that the majority of RORγt + ILC3s in the mLN were NCR − CCR6 + cells 7 which expressed high levels of CD1d (Fig 1D and E) and lymphotoxin‐alpha ( LTA ) mRNA but lacked T‐bet (Fig EV1C and D). Within the SI‐LP, we found low CD1d expression in NCR + and NCR − CCR6 − ILC3s in comparison with NCR − CCR6 + cells (Fig 1D and E).…”
Section: Resultssupporting
confidence: 76%
“…To interrogate the levels of CD1d expression in the different ILC3 subpopulations, we performed additional phenotypical analyses of ILC3s from different tissues (Figs 1D and E, and EV1, EV2 and EV3). As previously described, we found that the majority of RORγt + ILC3s in the mLN were NCR − CCR6 + cells 7 which expressed high levels of CD1d (Fig 1D and E) and lymphotoxin‐alpha ( LTA ) mRNA but lacked T‐bet (Fig EV1C and D). Within the SI‐LP, we found low CD1d expression in NCR + and NCR − CCR6 − ILC3s in comparison with NCR − CCR6 + cells (Fig 1D and E).…”
Section: Resultssupporting
confidence: 76%
“…This pathway may have implications for human disease as HLA‐DR expression on human intestinal ILC3 is reduced in paediatric Crohn's disease patients 55. MHCII + ILC3 migrate from the intestine to the mesenteric lymph node in a CCR7‐dependent manner, suggesting that antigens may be acquired locally in the tissue before migration to lymph nodes 94. Surprisingly, a dichotomous relationship between MHCII and IL‐22 expression was recently reported among intestinal ILC3,60 seemingly in contrast to previous reports that LTi‐like ILC3 are a dominant source of IL‐22 of the intestine56, 67, 97 (Fig.…”
Section: Ilc3 Interactions With Adaptive Immunitymentioning
confidence: 99%
“…Interestingly, some studies suggest that ILC, 129-131 basophils, [132][133][134] and eosinophils 135,136 can express major histocompatibility complex class II and directly prime Th2 responses, notably upon N. brasiliensis 131 and T. muris 132 infections, with each cell type having been shown to migrate to the mesenteric lymph nodes during infection. 85,87,137,138 However, given that protective immunity is abolished in mice where all 139,140 or specific subsets 104-106,108,109 of dendritic cells have been depleted, it is perhaps more likely that these other innate cells contribute to local tissue immunity by promoting dendritic cell activation, or by further enhancing the cytokine response of mature T cells that have migrated to the infected tissue. 53 Moreover, dendritic cells are responsive not only to cytokines produced by other innate cells, but also to epithelium-derived cytokines, including TSLP, 54,[141][142][143] IL-25, 144 and IL-33, 52,145 thus potentially bypassing ILC2 and granulocytes entirely.…”
Section: Inductionmentioning
confidence: 99%